ZnO/Carbon Spheres with Excellent Regenerability for Post-Combustion CO2 Capture - Iwona Pełech (MDPI AG, 2021)
This paper examines the synthesis of the ZnO/carbon spheres composites using resorcinol—formaldehyde resin as a carbon source and zinc nitrate as a zinc oxide source in a solvothermal reactor heated with microwaves. The influence of activation with potassium oxalate and modification with zinc nitrate on the physicochemical properties of the obtained materials and CO2 adsorption capacity was investigated. It was found that in the case of nonactivated material as well as activated materials, the presence of zinc oxide in the carbon matrix had no effect or slightly increased the values of CO2 adsorption capacity. Only for the material where the weight ratio of carbon:zinc was 2:1, the decrease of CO2 adsorption capacity was reported. Additionally, CO2 adsorption experiments on nonactivated carbon spheres and those activated with potassium oxalate with different amounts of zinc nitrate were carried out at 40 °C using thermobalance. The highest CO2 adsorption capacity at temperature 40 °C (2.08 mmol/g adsorbent) was achieved for the material after activation with potassium oxalate with the highest zinc nitrate content as ZnO precursor. Moreover, repeated adsorption/desorption cycle experiments revealed that the as-prepared carbon spheres were very good CO2 adsorbents, exhibiting excellent cyclic stability with a performance decay of less than 10% over up to 25 adsorption-desorption cycles.